Liquidity, Solvency, and Asset Growth Effects on Stock Prices: The Mediating Role of Profitability in Transportation and Logistics Companies Listed on the Indonesia Stock Exchange (2019–2024) - Lisdiana, Vera; Hari Gursida; Yohanes Indrayono (Asosiasi Ahli Administrasi Indonesia, 2026)
This study investigates the effects of liquidity, solvency, and asset growth on stock prices, both directly and indirectly through profitability as a mediating variable, in transportation sector companies listed on the Indonesia Stock Exchange during 2019–2024. Liquidity is measured using the Current Ratio (CR), solvency using the Debt-to-Equity Ratio (DER), asset growth through annual asset growth, profitability using Return on Assets (ROA), and stock prices based on closing prices. A quantitative approach employing panel data regression analysis is applied, while the mediating role of profitability is examined using the Sobel test. The findings indicate that liquidity and asset growth have positive and significant effects on stock prices, whereas solvency has a negative effect. Liquidity and asset growth also positively influence profitability, while solvency negatively affects profitability. Profitability significantly increases stock prices and mediates the relationships between liquidity and stock prices as well as asset growth and stock prices. However, profitability does not mediate the effect of solvency on stock prices. These results emphasize the importance of effective liquidity management and asset utilization in enhancing profitability and firm market value, while excessive leverage may weaken investor confidence.